Evaluation of the Internal Control System Implementation in Credit Card Provision at Bank Rakyat Indonesia’s Regional Offices - Helmi, Sulaiman; Septiani, Putri; Rianawati, Dian; Sartika, Dewi; Apandi (Sinergi International Journal of Management and Business, 2024)
Credit is one of the largest and most important components of wealth compared to other assets. Therefore, to obtain maximum interest (income) from the loan, the bank concerned must pay special attention to the loan. Therefore, a good management system, such as a management system called internal control, is one of the most important factors in business success. Internal control is policies and mechanisms, other than accounting system control, which are created by management with the belief that the company's goals will be achieved, so that good internal control will bring benefits to business activities, and all activities can be controlled well. This study investigates the implementation of internal control systems in credit provision at Bank Rakyat Indonesia Regional Office (BRI RO) Palembang, emphasizing their critical role in maximizing interest income from loans. Using a qualitative descriptive approach, the research assesses the effectiveness of COSO's five control components control environment, risk assessment, control activities, information and communication, and monitoring. Despite challenges, the study finds that internal controls are effective, supported by skilled employee competencies aligned with their responsibilities. The findings underscore the significance of robust internal control practices in enhancing credit management efficiency and mitigating risks. This research provides practical insights for improving internal control mechanisms to optimize credit operations and ensure financial stability at BRI RO Palembang.